Diseconomies of Managing in Acquisitions: Evidence from Civil Lawsuits - Shaver, J. Myles; Mezias, John M. (Organization Science, 2009)
The difficulties of managing and coordinating operations as firms expand are expected to increase disproportionately with firm size. If firms face such diseconomies of managing, then acquisitions should make the combined entity more difficult to manage than the two entities operating independently. To document the existence of diseconomies of managing in acquisitions, we examine the change in civil lawsuit judgments involving acquired firms pre- and postacquisition. Civil lawsuit judgments can capture breakdowns in management oversight that cause firms to take actions that a prudent firm would not take or fail to take actions that a prudent firm would take. We find that acquired entities face a significant increase in lawsuit judgments postacquisition. We describe why our findings provide evidence of diseconomies of managing and highlight why managerial diseconomies should be an important consideration when managing or examining acquisition strategies.